2015
DOI: 10.1513/annalsats.201501-032ot
|View full text |Cite
|
Sign up to set email alerts
|

Training the Teachers. The Clinician-Educator Track of the University of Washington Pulmonary and Critical Care Medicine Fellowship Program

Abstract: The University of Washington was the first pulmonary and critical care medicine fellowship training program accredited by the Accreditation Council for Graduate Medical Education to create a dedicated clinician-educator fellowship track that has its own National Residency Matching Program number. This track was created in response to increasing demand for focused training in medical education in pulmonary and critical care. Through the Veterans Health Administration we obtained a stipend for a clinician-educat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…Participants provided informed consent at the time of their enrolment. We chose topics to provide a sampling of those in similar programmes, emphasising career development and teaching strategies . The sessions included:…”
Section: Methodsmentioning
confidence: 72%
“…Participants provided informed consent at the time of their enrolment. We chose topics to provide a sampling of those in similar programmes, emphasising career development and teaching strategies . The sessions included:…”
Section: Methodsmentioning
confidence: 72%
“…A study showed that "resident as teachers" curricula (residency integrated programs focusing on teaching) significantly improve teaching abilities, reinforce resident knowledge, and bolster postresidency placement. 4,7 Accordingly, neurology training programs (e.g., UCLA, Yale) are beginning to offer longitudinal clinical-educator tracks (combining didactic series, education electives, leadership of small groups, bedside teaching, and mentored scholarly projects) within the residency. Ideally those developing educational tracks will reflect the AAMC's findings that relationship-based, noncognitive skills are a core feature of effective teaching, 8 and include enhancement of a resident's "softer" skills, including leadership by example, teacher-student communication, and providing feedback, not just theoretical knowledge.…”
Section: Training Opportunities In Neurology Residencymentioning
confidence: 99%
“…A number of articles lament the difficulty of using T-32 or R25 grants in fellowship toward a clinician educator path. 7 A review of Google (search terms: "neurology medical education fellowship," "neurology education fellowship"), the AAN fellowship directory, ACGME, and United Council for Neurologic Subspecialties databases showed only 1 neurology-specific education fellowship. The AAN Institute Medical Educator fellowship 10 is a research-based, stipend fellowship for AAN members who have completed neurology/child neurology or neurodevelopmental disabilities residencies or fellowship in the last 5 years.…”
Section: Postgraduate Training Opportunitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Not every fellow needs formal education training; however, fellows who wish to become clinician educators should consider formal training opportunities. These include a variety of activities, including advanced degrees in medical education or fellowship tracks designed specifically to produce specialists not only in pulmonary and critical care, but also in education (one example is the University of Washington's clinician educator fellowship 5 ).…”
Section: Responsementioning
confidence: 99%